Brain drain in developing regions (1990 - 2000) - Frédéric Docquier; Olivier Lohest; Abdeslam Marfouk (Institute for the Study of Labor (IZA), 2005)
In this paper, we analyze the distribution of the brain drain in the LAC region (Latin America and the Caribbean), Asia and Africa. We rely on an original data set on international migration by educational attainment for 1990 and 2000. Our analysis reveals that the brain drain is strong in Eastern, Middle and Western Africa, Central America and the Caribbean. However, the Kernel approach suggests that the dispersion and the intradistribution dynamics of skilled migration rates strongly differ across regions. We then tautologically disentangle the brain drain into two multiplicative components, the global migration rate and the selection bias. Among the most affected countries, LAC countries suffer from high migration rates whilst most African countries suffer from high selection biases. Finally, exploratory Moran's tests reveal strong spatial, political and cultural autocorrelations in migration rates and selection biases. The latter result suggests that skilled workers react differently than unskilled workers to a large set of variables.
Keywords: F22; O15; J11; J24; 330; international migration; brain drain; human capital; spatial autocorrelation